Vertebral Fracture Assessment in Postmenopausal Women with Low Bone Mass: Prevalence and Risk Factors - Teeyasoontranon, Waralee; Kaewchur, Tawika; Namwongprom, Sirianong; Chatnampet, Ketnapa; Ekmahachai, Molrudee (Biomedical Sciences and Clinical Medicine, 2019)
Objective The study aimed to use VFA to determine the prevalence of and risk factors associated with unnoticed VFs in postmenopausal women with low bone mass. Methods A total of 330 consecutive postmenopausal patients with a mean age of 62.7 years (range 43 to 85 years) who had been diagnosed with low bone mass by bone mineral densitometry (BMD) with a T-score between -1.0 and -2.5 and who had undergone VFA study were retrospectively reviewed. No prior vertebral or non-vertebral fragility fractures had been observed in any of the patients. The VFAs were performed in a supine position using Hologic Discovery A. VFA interpretation was done independently by two experienced nuclear medicine physicians using a combination of the Genant visual semi-quantitative method and morphometric measurement. Demographic data from the medical records and questionnaires were reviewed. Results The prevalence of VFs was 25.8%. Of those, 9.1% had Grade 1 and 16.7% had Grade 2 and/or 3 fractures. VFs were identified in 165 vertebrae of 85 patients who had VFs. Of which 49.7% were wedge and 50.3% were biconcave fractures but without crush fracture. The thoracolumbar junction (T11-L2) was the most common site of VFs. The interobserver agreement between the two nuclear medicine physicians was very good (Cohen’s kappa=0.89). Age, years since menopause, and steroid use were identified as independent risk factors. Conclusion As VFA detected unnoticed VFs in one fourth of postmenopausal women with low bone mass, an additional VFA at the time of BMD study should be considered for this group of patients